PELAKSANAAN PEMBELAJARAN PENDIDIKAN AGAMA ISLAM OLEH GURU SEKOLAH DASAR PADA GUGUS I LUBUK SIKARAH KOTA SOLOK - Yulmida AM (al-fikrah: Jurnal Manajemen Pendidikan, 2016)
Implementation of Islamic Education Teaching in Primary School Cluster I Lubuk Sikarah Solok. Thesis Magister Program of Management of Islamic Education at Post Graduate Program State College of Islamic Studies (STAIN) Batusangkar, 2014. Cluster I Lubuk Sikarah Solok City is one of the existing Primary School Cluster with a focus to create the best performing students, berbudii noble character, morality based on religious values  and customs with the steps instill a sense of faith, morality, and religion God Almighty, improve discipline each school community, improving the professionalism of teachers, educators complementary infrastructure, involving the whole element involved in education to participate actively in order to achieve educational goals.This study aims to describe the habits of Islamic religious education teachers in preparing lesson plans, habits Islamic religious education teachers in the implementation of learning, habits of Islamic religious education teachers in the evaluation of learning outcomes. This study is an ethnographic research design that uses a qualitative approach with descriptive method of analysis. Data was collected by (1) observation; (2) interview; (3) documentation. Key informants collected by sampling jugmen while additional informants by means of snowball sampling. The results of this study are: (1) Islamic religious education teachers have been professional in preparing lesson plans, (2) Islamic religious education teacher has been a professional in the implementation of learning, (3) Islamic religious education teacher has been a professional in the evaluation of learning outcomes.Kata Kunci: Pembelajaran, Pendidikan Agama Islam, guru